Relationship between healthcare seeking and pain expansion in patients with nonspecific chronic low back pain - Mónica Grande-Alonso; Daniel Muñoz-García; Ferran Cuenca-Martínez; Laura Delgado-Sanz; María Prieto-Aldana; Roy La Touche; Alfonso Gil-Martínez (PeerJ, 2020)
Objectives Low back pain (LBP) is the most prevalent musculoskeletal problem, which implies a high rate of chronicity. The chronicity of symptoms can lead to pain expansion. The main objective of this study was to assess whether there were differences between patients with nonspecific chronic LBP (CLBP) who sought healthcare compared to those who did not in terms of pain expansion. Methods Ninety individuals participated in the study and were divided into three groups: 30 patients who sought care; 30 patients who did not seek care; and 30 asymptomatic individuals. The primary variable analyzed was pain expansion. Secondary physical and psychological variables were assessed later, and a regression analysis was performed. Results Patients who sought help showed significant differences in pain expansion and pain intensity compared with the group who did not seek help, with a medium effect size (0.50–0.79). The regression model for the care-seeking group showed that dynamic balance with the left leg and depression were predictors of percentage pain surface area (34.6%). The combination of dynamic balance, range of movement in flexoextension and depression were predictors of widespread pain (48.5%). Conclusion Patients who soughtcare presented greater pain expansion than patients whodidnot. A combination of functional and psychological variables can significantly predict pain expansion in patients with nonspecific CLBP who seek help.